Planning support systems and smart cities - Geertman, Stan; Ferreira, Jr.; Goodspeed, Robert; Stillwell, John (Lecture Notes in Geoinformation and Cartography, 2015)
This book is a selection of the best and peer-reviewed articles presented at the CUPUM (Computers in Urban Planning and Urban Management) conference, held in the second week of July 2015 at MIT in Boston, USA. The contributions provide state-of the art overview of the availability and application of Planning Support Systems (PSS) in the framework of Smart Cities